THE HELMHOLTZ, THE DOCTOR, THE MINOTAUR, AND THE LABYRINTH. - AKGÜN, BUKET (Mythlore)
The article compares the use and resolution of the hero Minotaur and the monster Labyrinth themes and imagery in Victor Pelevin's novel "The Helmet of Horror" and the sixth season of Toby Whitehouse's "Doctor Who" episode "The God Complex." Topics discussed are the tribunal sacrifice substituted by the eight kidnapped characters in the novel, different receptions of the different civilizations and cultures notably the labyrinth of Crete, and the combining of myths and contemporary culture.